Neutrophil gelatinase-associated lipocalin production negatively correlates with HK-2 cell impairment: Evaluation of NGAL as a marker of toxicity in HK-2 cells - Hauschke, Martina; Roušarová, Erika; Flidr, Pavel; Čapek, Jan; Libra, Antonín; Roušar, Tomáš (My University, 2017)
Neutrophil gelatinase-associated lipocalin is an extracellular protein produced mostly in kidney. Recently, it has become a promising biomarker of renal damage in vivo. On the other hand, the validation of NGAL as a biomarker for nephrotoxicity estimation in vitro has not been characterized in detail yet. Since the HK-2 cells are frequently used human kidney cell line, we aimed to characterize the production of NGAL in these cells and to evaluate NGAL as a possible marker of cell impairment. We used heavy metals (mercury, cadmium), peroxide, drugs (acetaminophen, gentamicin) and cisplatin to mimic nephrotoxicity. HK-2 cells were incubated with selected compounds for 1-24h and cell viability was measured together with extracellular NGAL production. We proved that HK-2 cells possess a capacity to produce NGAL in amount of 2pg/ml/h. We found a change in cell viability after 24h incubation with all tested toxic compounds. The largest decrease of the viability was detected in mercury, acetaminophen, cisplatin and gentamicin. Unexpectedly, we found also a significant decrease in NGAL production in HK-2 cells treated with these toxins for 24h: to 11±5%, 54±5%, 57±6% and 76±9% respectively, compared with controls (=100%). Our results were followed with qPCR analysis when we found no significant increase in LCN2 gene expression after 24h incubation. We conclude that extracellular NGAL production negatively correlates with HK-2 cell impairment.
NGAL produkce negativně koreluje s poškozením HK-2 buněk.
Keywords: Cell viability; HK-2 cells; In vitro nephrotoxicity; NGAL; Nephrotoxicity markers; Viabilita buněk; HK-2 buňky; in vitro neforotoxicita; NGAL; markery nefrotoxicity